Do patients’ understanding of diabetes and perception of control predict higher Hba1c and complications? - Chin, Sze Paw; Che Abdullah, Shahrin Tarmizi; How, Soon Hin; Satwi, Sapari; Abdul Kadir, Khalid (Faculty of Medicine, International Islamic University Malaysia, 2006)
Patient understanding and perception of diabetes control is important if clinicians were to allow diabetes patients to play a central role in management of their illness. We conducted a survey to see what diabetic patients generally thought of their understanding of disease and glycemic control; if these perceptions were accurate and related to complications. One hundred and eight consecutive patients (mean age 52.7± 13 years, BMI 27±5.2 kg/m2, HbA1c 9.2±2.2 %) attending diabetes clinic participated including 63% women, 60% primary or no education, and 47% duration of diabetes >10 years. 54% claimed to have a good understanding although nearly half answered questions on diabetes management and targets wrongly. 32% perceived their glycemic control to be good and were found to have lower baseline HbA1c (p<0.001), shorter duration of disease (p= 0.013), fewer or no complications (p= 0.06) and smaller 6-month deteriorations in HbA1c (p= 0.024) than patients who perceived poor control. Half of the patients over-estimated their control. Patients who wrongly perceived their diabetes control had significantly higher BMI (p <0.0001). 60% did not known they have diabetic complications. Patient understanding of diabetes remains poor. Continuing patient education is important. Patient perception of glycemic control is also poor and inversely related to complications and deterioration of HbA1c. Overweight patients are more likely to perceive glycemic control wrongly.